European raw materials policy — past and current development - Hans R. Krämer (Intereconomics, 1977)
In world-wide negotiations and agreements on raw material problems the Community is either taking part as such or represented by the member state providing the Chairman of the Council. Admittedly it has often been difficult to work out the required common position for the member states, and only insofar as a consensus has been reached between them can therefore be talked of a European Raw Material Policy.
Keywords: 330; Raw Materials